A new split‐luciferase complementation assay identifies pentachlorophenol as an inhibitor of apoptosome formation - Amin Tashakor; Mahshid H‐Dehkordi; Enda O'Connell; Sergi Gomez Ganau; Rafael Gozalbes; Leif A. Eriksson; Saman Hosseinkhani; Howard O. Fearnhead (FEBS Open Bio)
The expense and time required for in vivo reproductive and developmental toxicity studies have driven the development of in vitro alternatives. Here, we used a new in vitro split luciferase‐based assay to screen a library of 177 toxicants for inhibitors of apoptosome formation. The apoptosome contains seven Apoptotic Protease‐Activating Factor‐1 (Apaf‐1) molecules and induces cell death by activating caspase‐9. Apaf‐1‐dependent caspase activation also plays an important role in CNS development and spermatogenesis. In the in vitro assay, Apaf‐1 fused to an N‐terminal fragment of luciferase binds to Apaf‐1 fused to a C‐terminal fragment of luciferase and reconstitutes luciferase activity. Our assay indicated that pentachlorophenol (PCP) inhibits apoptosome formation, and further investigation revealed that PCP binds to cytochrome c. PCP is a wood preservative that reduces male fertility by ill‐defined mechanisms. Although the data show that PCP inhibited apoptosome formation, the concentration required suggests that other mechanisms may be more important for PCP's effects on spermatogenesis. Nonetheless, the data demonstrate the utility of the new assay in identifying apoptosome inhibitors, and we suggest that the assay may be useful in screening for reproductive and developmental toxicants.